Systematic Literature Review: Mathematical Reasoning Ability in Mathematics Learning - Deby Ashri Khardita; Arief Agoestanto (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2023)
Many studies discuss the effect of mathematical reasoning on learning mathematics. Collecting and analyzing the results of this research needs to be done in order to get an idea of how mathematical reasoning influences the learning of mathematics. The Systematic Literature Review (SLR) method is used to synthesize studies that are relevant to the purpose of this study. By using the Google Schoolar, Libgen, Science Direct search engines, 20 articles published from 2016 to 2022 were included in the criteria which were then analyzed further. The results of the research show that mathematical reasoning can improve mathematics learning